Un humor de izquierda. Melancolía materialista de César Aira - Alejandro Fielbaum (Cuadernos LIRICO)
From the mentions to the humoristic figure of the Schlemihl in the works of Marx, Derrida, Gramsci and Benjamin, we read with Freud the melancholic thematization of the subject in the contemporary left. The work of César Aira allows us to think of a certain articulation between materialism and melancholy, through which Aira positions himself in Argentine narrative as the inventor of other worlds in the world that, time and again, is lost. Humor opens the option of a serious position in front of language without certainty, option whose politics passes through a non-individual opening of the language, capable of tracing ghosts.